The Influence of the Learning Process Quality on the Learning Outcomes of West Sumatra High School Students: Student Engagement and Charismatic Leaders as Moderators - Fiza, Nailil; Susanto, Perengki (FKIP Universitas Lampung, 2024)
This study aims to determine the effect of Student Engagement and Charismatic Leaders in moderating the relationship between the quality of the learning process and the learning outcomes of students at SMAN 1 West Sumatra. The sample was 273 students of SMAN 1 West Sumatra who were taking the teaching and learning process at that time. This study used a census sample technique. This type of research is quantitative research. The data collection technique used a questionnaire with a Likert scale model with 5 alternative answers. Data analysis was carried out using Sem-PLS 4. The results of the study showed that The Quality of the Learning Process had a significant effect on the learning outcomes of students at SMAN 1 West Sumatra. Furthermore Student Engagement had a positive and significant effect in moderating the relationship between the Quality of the Learning Process and learning outcomes. Finally Charismatic Leaders had a positive and significant effect in moderating the relationship between the Quality of the Learning Process and the learning outcomes of students at Senior High School N 1 West Sumatra.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.154-164